2021
DOI: 10.1038/s41598-021-96627-7
|View full text |Cite
|
Sign up to set email alerts
|

Tau K321/K353 pseudoacetylation within KXGS motifs regulates tau–microtubule interactions and inhibits aggregation

Abstract: Alzheimer’s disease is the leading cause of dementia and a defining hallmark is the progressive brain deposition of tau aggregates. The insidious accumulation of brain tau inclusions is also involved in a group of neurodegenerative diseases termed frontotemporal dementias. In all of these disorders, tau aggregates are enriched in post-translational modifications including acetylation, which has recently been identified at multiple sites. While most evidence suggest that tau acetylation is detrimental and promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Mouse monoclonal antibodies, CP27 and PHF-1 were generous gifts from the late Dr. Peter Davies [ 26 , 60 ]. Total Tau 3026 rabbit polyclonal antibody was previously described [ 68 , 81 ]. Mouse monoclonal antibody Tau-5 was purchased from Invitrogen (Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse monoclonal antibodies, CP27 and PHF-1 were generous gifts from the late Dr. Peter Davies [ 26 , 60 ]. Total Tau 3026 rabbit polyclonal antibody was previously described [ 68 , 81 ]. Mouse monoclonal antibody Tau-5 was purchased from Invitrogen (Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Acetylation of K280 and K321 may exhibit a distinct effect on the aggregation of tau. Previous studies have reported that K280 acetylation increases the aggregation of tau, , while some experimental works demonstrated the protective effects against tau aggregation by K321 acetylation. , To elucidate the underlying mechanisms by which acetylation affects tau aggregation at the atomic level, we performed 500 ns REMD simulations on the R2 dimer with acetylated K280 and the R3 dimer with acetylated K321. We first explored the influence of K280 acetylation on the conformational ensembles of the R2 dimer by calculating the average probability of each type of secondary structure and residue-based β-sheet probability in the R2 and R2-K280 systems.…”
Section: Resultsmentioning
confidence: 99%
“…Although most evidence suggests that tau acetylation contributes to disease, several studies have reported that specific acetylation sites, e.g., lysine 321 (K321), could be protective in tau aggregation. , Previous in vitro experiments revealed that tau acetylation on K321 could significantly impede tau filament assembly and inhibit phosphorylation on serine 324 . Xia et al pointed out that single acetylation site at either K321 or K353 could be sufficient to prevent or slow the formation of tau filaments, which may represent a natural protective mechanism against tau aggregation . Despite these studies, the underlying molecular mechanisms by which acetylation of tau protein at the K280 or K321 site affects tau aggregation are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“… 49 While some groups report a protective effect of HDAC6, 50 others suggest that inhibiting this protein can lead to improvement. 51 , 52 Some of these effects might be cell line specific or more relevant for certain tau isoforms, which adds another layer of complexity. The N2a cells used in this study represent a simple and robust model, which expresses many different tau isoforms.…”
Section: Discussionmentioning
confidence: 99%